The Influence of Meteorological Factors on Tropospheric Refractive Index over Indonesia - Bayong Tjasyono HK.; Djakawinata S. Djakawinata S. (Institut Teknologi Bandung, 1999)
Since the troposphere is a non homogeneous medium with vertical variation of meteorological factors, it would be expected vertical gradients of the refractive index and, as a result, a refration of radio waves. This study higlights results of the radiosonde observations in Serpong, West Java. The results show that the refractive index decreases with altitude and in the lower troposphere, this index has a diurnal fluctuation due to the variation of meteorological factors.